Noninvasive Vascular Diagnosis A Practical Guide to Therapy - AbuRahma, Ali F.; Bandyk, Dennis F.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
There has been a rapid expansion in the field of noninvasive vascular diagnostics over the past two decades. Technological advances have provided an unprecedented variety of therapeutic options and the contemporary vascular specialist today must provide the entire spectrum of care for the patient with circulatory disease, including conventional open surgery, minimally invasive endovascular therapy, and medical management. This new edition of Noninvasive Vascular Diagnosis provides truly comprehensive coverage of noninvasive vascular testing, ranging from conventional noninvasive technology to the latest state-of-the-art advances. Regulatory issues are also discussed, which will become an increasingly important issue in our evolving health care system. It is designed to help determine the most applicable and practical methods for managing patients in the most cost effective and efficient manner. A considerable amount of new material has been added to this popular textbook and there has been extensive revision of its previous content. The Editors have gathered together prominent experts in the field to address the needs of all clinicians who are involved in the care of patients with vascular disease, continuing to make this a key reference in the field.
Keywords: Medicine; Diagnosis, Ultrasonic; Internal medicine; Heart -- Surgery; Vascular Surgery; Medicine & Public Health; Vascular Surgery; Ultrasound; Cardiac Surgery; Internal Medicine